AN ANALYSIS OF STUDENTS’ ABILITY AND DIFFICULTY IN WRITING DESCRIPTIVE TEXT - Anhar, Andi Fausia; Abduh, Amirullah; Aeni, Nur (Universitas Negeri Makassar, 2022)
This study is qualitative descriptive research that aims to analyze the student’s ability and difficulty in writing descriptive text in Second grade students of MTs Darul Istiqomah Makassar as a sample of this research. The instruments of this researcher were writing test and interview to help the researchers gain the data. A writing test was used to see the students’ ability in writing descriptive text. Moreover, an interview was used to see the students’ difficulty in writing descriptive text. Based on the analysis of five elements of writing, such as content, organization, vocabulary, grammar, and mechanics, it was found that the students still have many errors or difficulties in their writing. Especially in the Grammar category (85%) and Vocabulary category (69%). As a result, the students got a poor score. In addition, the result of the interview showed that students have some difficulties in writing descriptive text. Especially on the grammar used (in this case, simple present tense and word choice – lack of vocabulary). Moreover, most students had difficulty creating good sentences/paragraphs and writing with correct spelling words, punctuation, and capitalization. It showed that the students still need to pay attention to all those five elements in writing.